(untitled) (Research, Society and Development, 2019)
Objective: To investigate the formulation of green banana biomass products and their potential for industry and health. Method: This is an integrative review article based on a survey of scientific articles available in the Medline, Scielo and Pubmed databases using the following descriptors’ Biomass’, ’Resistant Starch’, ’Green Banana,’ Nutrition ’ , ’Products’ both used alone or in combinations in the Portuguese and English languages. Results: Five articles were selected where biomass was used in Kefir, pasta, cakes and breads. It can be seen that in recent years the green banana has aroused interest from the consumer market, mainly due to its high nutritional value, presence of resistant starch, compounds and antioxidant capacity besides having a good sensory acceptance. Conclusion: Green banana biomass and its byproducts have great potential to be used in bread, cake and various pasta formulations, and can contribute significantly to improve the nutritional aspects of products widely consumed by the population.